PEMANFAATAN TEKNOLOGI MEDIA UNTUK MENGEMBANGKAN LAYANAN KONSELING BAGI PESERTA DIDIK - Suprianto Baen; Herdi Herdi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This study aims to utilize media technology to develop counseling services for students. The method used is a literature review study, articles are searched through the database using Google Scholar, which were published from 2019 to 2023 and were written in English and Indonesian. Based on the data synthesis, 19 selected articles were studied and input prepared by the reviewers for analysis. design, along with the results and conclusions of each paper. Qualitative, quantitative research and review articles are included to have a broader picture of this subject. The results of this study are good language skills, this is a source of strength from implementing online counseling using chat features good language skills, this is a source of strength from implementing online counseling using chat features the use of information technology can improve planning and career maturity in students. Online counseling takes the form of virtual e-counseling technology media in the form of: websites, telephone/mobile phones, email, video conferencing, chat, instant messaging, computers and other social media networks which are now growing more and more easily accessible via smartphones. The survey shows that the type of counseling media application feature that is most widely used by students and counseling teachers is chat (93.75%). BK teachers about the duration of online counseling that students often do between 20-60 minutes, reported by 57.5% of counseling teachers.